Change Management in Information System Projects Implementation in Government Organizations - Jayson Tamayo (Southeast Asian Journal of Science and Technology, 2017)
Successful implementation of Information Systems has been a challenge to any organization, whether it is government or privately owned. Several governments have invested big amount of money on Information Systems (IS) however, most of the projects failed to be implemented successfully due to the lack of Change Management (CM). This paper aims to document the Change Management (CM) concepts being used by other government-owned offices and organizations. Through extensive literature review, the Change Management (CM) concepts, applications and methods being used by government organizations are discovered. This paper will serve as a reference to other government agencies planning to implement an Information System (IS) project.